The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4049/jimmunol.180.5.3132
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced IFN-γ Production within the Tumor Microenvironment Influences Antitumor Immunity

Abstract: Alterations to the tumor microenvironment following localized irradiation may influence the effectiveness of subsequent immunotherapy. The objective of this study was to determine how IFN-γ influences the inflammatory response within this dynamic environment following radiotherapy. B16/OVA melanoma cells were implanted into C57BL/6 (wild-type (WT)) and IFN-γ-deficient (IFN-γ−/−) mice. Seven days after implantation, mice received 15 Gy of localized tumor irradiation and were assessed 7 days later. Irradiation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
328
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(342 citation statements)
references
References 49 publications
(50 reference statements)
11
328
1
2
Order By: Relevance
“…6,1517 Investigations in different mouse tumor models revealed that radiotherapy-induced anti-tumor immune reactions, which are essentially dependent on type-I interferons (produced by the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) axis), APCs, and cytotoxic CD8 + T cells, are exclusively stimulated by high single doses (10–20 Gy). 1823 On the contrary, a recent study suggests that 3 × 8 Gy may be optimal. 24 Clinically, abscopal tumor lesion regression remains rare, most likely because comparable super-hypofractionated protocols (fractions of >5 Gy) are rarely used in the radiotherapeutic routine.…”
Section: Introductionmentioning
confidence: 99%
“…6,1517 Investigations in different mouse tumor models revealed that radiotherapy-induced anti-tumor immune reactions, which are essentially dependent on type-I interferons (produced by the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) axis), APCs, and cytotoxic CD8 + T cells, are exclusively stimulated by high single doses (10–20 Gy). 1823 On the contrary, a recent study suggests that 3 × 8 Gy may be optimal. 24 Clinically, abscopal tumor lesion regression remains rare, most likely because comparable super-hypofractionated protocols (fractions of >5 Gy) are rarely used in the radiotherapeutic routine.…”
Section: Introductionmentioning
confidence: 99%
“…35 IFN-γ has important effects in the tumour microenvironment, including the inhibition of cell proliferation and angiogenesis. 33 Investigations have revealed that epidural anaesthesia and spinal block may influence cytokine responses and inhibit tumour metastasis. 4,36 The present study showed higher serum concentrations of antitumourigenic IL-10 and IFN-γ, and lower serum concentrations of protumourigenic IL-1β and IL-8 at T 4 h , in patients who received combined general/epidural anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…32 In contrast, both IL-10 and IFN-γ are well known antitumour cytokines. 33,34 IL-10 exhibits antitumour and antimetastatic activity through enhanced NK cell lysis of tumour cells. 35 IFN-γ has important effects in the tumour microenvironment, including the inhibition of cell proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple smaller doses of radiation instead of the single dose were ineffective in slowing tumor growth, and chemotherapy administered after the single dose interfered with tumor regression and the associated immune response (4). Additional studies showed that radiation exposure increased tumor immunogenicity, stimulated antigen-presenting cells and promoted migration and entry of T cells into tumors (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, radiation can be used to enhance systemic T-cell antitumor immunity that can improve therapeutic efficacy (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Recent studies have shown that the ability of a single dose of radiation (20 Gy) to slow the growth of primary melanoma tumors is dependent on immune cells, since the slowing observed in wild-type mice failed to occur in immunodeficient nude mice, and slowing was abrogated by depleting the CD8 þ T cells of the tumor-bearing mice with monoclonal antibodies (4,5).…”
Section: Introductionmentioning
confidence: 99%